Analisa Total Productive Maintenance terhadap Produktivitas Kapal/Armada Menggunakan Metode Overall Equipment Effectiveness pada PT. Global Trans Energy International - Astrid Diandra Maulidina; Erry Rimawan; Muhammad Kholil (Universitas Bunda Mulia, 2017)
Industrial development in the coal mining sector is a government effort to increase the foreign exchange. By seeing the potential, the marine transportation service company for the bulk cargo of coal, the company has a problem that is often happening in customer satisfaction, one of it is low efficiency and effectivity of the ship due to incompetence in the maintenance management of the ship appropriately. By calculating the productivity of the ship by using Overall Equipment Effectiveness (OEE) method is expected to improve the efficiency and effectiveness of the ship. The measurement is done by calculating the level of Availability Rate, Performance Rate, and Quality Yield. From the measurement, we can see Six Big Losses to facilitate in identifying the causes of the productivity which is below the standard ideal value. During January - December 2014 Overall Equipment Effectiveness values are ranged from 73.63% to 88.05% with an average value 80.58%. This proves that the ship operations throughout 2014 have not reached the ideal state yet. Seen from the value obtained is lower than the ideal standard is ≥85%. The cause of OEE low value is due to the effect of idling and minor stoppages amounted to 2.69% and 1.91% losses breakdown caused by Human, Methods, Engineering, and Environment factors.Keywords: Efficiency, Effectivity, Productivity, Overall Equipment Effectiveness, Six Big Losses.